Análise molecular de grupos sanguíneos na Fundação Hemominas para a identificação de variantes raras - Amanda Assis Muniz (2019)
Compatibility of red blood cell (RBC) between donors and patients is important to reduce the risk of post-transfusion hemolytic reactions. Ensuring hemocomponents for individuals with rare erythrocyte phenotypes can be challenging, since it is difficult to characterize patients and identify compatible donors. This study aimed to implement on Fundação Hemominas (FH), the only public blood bank of Minas Gerais, molecular biology methods to assist in the characterization of donors and patients with rare RBC phenotypes. Regarding donor screening, methods based on real-time PCR were developed for genotyping of the DO*HY (Dombrock system) and DI*A/DI*B (Diego System) alleles in individual samples or in pools of five samples. Sensitive and reproducible methods were developed. The genotyping of 457 blood donors showed that the frequencies of the DI*A and DO*HY alleles in Minas Gerais (1.09% and 1.53%, respectively) are as low as those observed in other Brazilian regions. DI*A/DI*B genotyping was also performed for 58 blood donors phenotyped as Dia+. All these donors presented the genotype DI*A/DI*B, confirming the difficulty in obtaining Di(a+b-) donors in our population. Self-reported race/skin color data from blood donors were obtained from the FH database to assess its applicability in the screening rare donors. No significant differences were observed in the frequencies of the DI*A, DI*B and DO*HY, comparing the self-declared white donors with those black and brown. Wide variation in percentages of African and European genomic ancestry was observed in individuals of different genotypes or self-declared race/color groups. The only individual with a rare DO*HY/DO*HY genotype included in this study was self-declared white and had 43.5% African and 46.3% European genomic ancestry, although this allele is characteristic of African populations. Thus, while both self-reported race/color and certain blood group alleles are associated with ancestry, the use of ethnic-racial criteria to assist in screening rare donors in highly mixed populations can be challenging. For patients, molecular analyzes of the Gerbich, Diego, Vel and Duffy blood group systems were standardized and applied to the resolution of cases in which alloimmunization against high frequency RBC antigens was suspected. Seven patients were analyzed, and in four of them alloimmunization associated with a rare phenotype was confirmed. The results obtained were useful in elucidating these cases. Thus, we can conclude that the results obtained in this study are very useful and can be applied to improve transfusion safety in Minas Gerais. The tests developed in this study will be available for implementation at the Immunohematology Laboratory of the Fundação Hemominas, where they may be applied for screening and confirmation of rare RBC phenotypes in blood donor and recipient, in order to increase transfusion safety.